ANALISIS TINGKAT STRES KERJA PADA GURU TUNA GRAHITA DI SEKOLAH DASAR LUAR BIASA (SDLB) NEGERI PURWOSARI KUDUS - Ferlia, Devita Audry; Jayanti, Siswi; Suroto, Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Job stress is a response to someone’s adaptation because of the demands in the workplace, either psychological or physical that it is influenced by individual differences or psychological processes. The unsuitable workplace condition and the burden of teaching with the number of students which is beyond the applied ratio can influence teachers’ job stress. Teachers are faced with a situation where the burden of responsibility is received so hard, it triggers the job stress to the teachers. The purpose of this study was to analyze the level of job stress on teachers of mentally disabled in Purwosari Kudus State SDLB. This research was a qualitative descriptive. This research subject was classroom teachers of mentally disabled. There were seven teachers and two triangulation informants. Observation was made to observe teacher’s behavior during the learning process and the factors that c an cause stress. The level of job stress was measured using the Live Event Scale method. In-depth interviews were conducted with key informants and triangulation informant. They were conducted to find out the factors that cause job stress include intrinsic factor in a job, individual role in organization, career development, relationships in the organizational structure and climate as well as the demand beyond the work. The research results showed that four informants experienced mild stress and three informants experienced severe stress. School should rearrange the classroom design to make the ongoing learning activities be comfortable. For teachers of mentally disabled who are not from PLB department should join special training programs organized by the provincial agencies.